EXPLORING THE BUSINESS POTENTIAL OF REFILL DRINKING WATER BUSINESS - Fauzi, Agung Rasi; Wardianto, K. Bagus; Nugeraha, Prasetya (Jurusan Administrasi Bisnis, FISIP, Universitas Lampung, 2023)
The purpose of this study was to determine the feasibility of the business of Refillable Water in Purwosari Village, Central Lampung in terms of non-financial aspects, namely legal aspects, market and marketing aspects, technical and technological aspects, environmental aspects as well as economic and social aspects and financial aspects which were analyzed using the method. payback period (PP), net present value (NPV), internal rate of return (IRR), and modified internal rate of return (MIRR).The existence of water is very important for all living things on earth. The existence of water is very important because its various benefits can affect a number of vital activities carried out by living things, especially humans to survive. Almost all activities carried out by humans always need water. Human needs for water are also very diverse, ranging from use for drinking water, cooking, bathing, washing, and other activities. The most important and vital use of water for humans is its function as drinking water. The results of this study indicate that: In terms of legal aspects, the business of refill drinking water in Purwosari Lampung village is feasible to run, In terms of market and marketing aspects, the business of refilling drinking water in Purwosari Village Lampung is declared very feasible to run. In terms of technical and technological aspects, the business of refilling drinking water in the village of Purwosari Lampung Tengah is very feasible to run, In terms of environmental aspects, the business of refilling drinking water in Purwosari Lampung Village is declared very feasible to run, In terms of economic and social aspects, the business of refilling drinking water in Purwosari Lampung village is being declared very feasible to run and In terms of financial aspects, the business of refilling drinking water in Purwosari Lampung village is declared very feasible to run.